THE ROLE OF DIGITAL BANKING IN ENHANCING OPERATIONAL EFFICIENCY IN INDIAN BANKS - Dixit, Shubham; Pandey, Pankaj (ShodhKosh: Journal of Visual and Performing Arts, 2023)
To provide a well-rounded understanding of how digital banking enhances operational efficiency, the research analyzes case studies and performance data from major Indian banks. These examples illustrate how successfully implementing digital banking strategies has led to greater efficiency, cost reductions, and improved customer satisfaction. For example, banks utilizing AI-driven customer service platforms have seen much faster resolution of customer issues, which boosts customer retention. Similarly, the introduction of mobile banking apps has significantly reduced the need for in-person visits, enabling banks to optimize staffing and reduce operational expenses. The paper also explores the broader competitive landscape of India's banking industry, where adopting digital banking is key to staying competitive. Banks that fail to embrace digital transformation risk losing market share to more technologically advanced competitors. This competitive pressure compels banks to continuously innovate and invest in digital infrastructure to remain competitive in the marketplace. The study's findings highlight that the adoption of digital banking technologies is crucial for improving the operational performance of Indian banks. These digital solutions not only allow banks to function more efficiently but also enhance profitability by cutting costs and improving customer satisfaction. As digital banking continues to evolve, its role in shaping the future of India's banking sector will become even more critical, emphasizing the need for ongoing investment and innovation.